Addendum to A Note on the 25 Most Frequent Surnames from the 2000 United States Census Bureau List. (2nd October 2017) - Nuessel, Frank
Abstract : This addendum to Nuessel discusses very recently released results on surname frequency in the US provided by the US Census Bureau. That bureau said that it would no longer prepare an updated list of the 1, 000 most frequent surnames in the US because of limited resources. In late 2016, the US Census Bureau released these data from the 2010 census. This note provides information based on that unanticipated release.